Research of Structural Quality of Big-Size KDP Crystals - Salo, V.I.; Tkachenko, V.F.; Puzikov, V.M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2008)
The faulted structure formation at a rapid growing of big-size KDP crystals has been analyzed. A transitional zone with high degree of lattice faultness has been revealed between the seed and the pure zone of the grown crystal by X-ray diffraction methods with high resolution. It has been determined that, regardless of the seed form, the transitional layer in grown crystals reaches the value of~12 mm. The nonmonotone variation of the crystal lattice parameter (∆d/d) within ±2.5·10⁻⁵ and the halfwidth of a diffraction reflection curve (β = 5.5÷8 arcs for direction [103] and β = 7÷9 arcs for direction [100]) and the increase of the integral power of reflection of the X-ray beam IR by 1.5 times are observed in the transitional lay